The influence of PMS and PDS oxidants on reaction rate of photocatalytic degradation of p-cresol over TiO2 powder - Advanced Oxidation Process - Varma, M. Surendra; Suresh, S. (The journal of contemporary issues in business and government, 2023)
The degradation of p-cresol is approved out under UV-visible light by TiO2 as a photocatalyst. In the direction of determining the efficiency of the photocatalyst, the, unlike variables, studied built-in the amount of photocatalyst, consequence of oxidants peroxomonosulphate (PMS) and peroxodisulphate (PDS) on the photocatalytic oxidation of p-cresol on elucidation TiO2 surface have been investigating. The efficiencies of these oxidants on photocatalytic degradation of p-cresol are compared with that of PMS and PDS.The investigational results indicate that these oxidants reveal improved rates of mineralization of p-cresol. A response mechanism, linking the production of hydroxyl radicals and sulfate radicals. In conclusion, this investigation indicated a high potential of TiO2 suspension to remove the high-level concentration of p-cresol under UV radiation.